Wide-azimuth anisotropic inversion based on rock physics model and its application in fractured reservoirs prediction in tight sandy conglomerate - Wei, Xinwei; Gao, Qiuju (Frontiers in Earth Science, 2025)
The study area is located in the north of an oil field in eastern China. Most of the middle and shallow sandy and gravelly rock mass development areas in this region have been identified, while the western section of the middle and deep sandy and gravelly rock mass development area has a large amount of reserves awaiting upgrading, and there is a reserve blank area of nearly 150 square kilometers in the central and eastern parts. The daily oil test output of the target layer section of the key well in the study area reached over 20 tons, confirming that the middle and deep layers still have good exploration potential. However, there are challenges such as deep burial depth, dense physical properties, rapid lateral variations, strong heterogeneity, and difficulty in seismic identification of nearshore fan and turbidite fan sandy conglomerate reservoirs. Conventional inversion methods struggle to precisely identify effective reservoirs under these conditions. Therefore, it is essential to conduct research on seismic anisotropic inversion method for tight sandy conglomerate reservoirs. This study aims to precisely delineate the distribution of effective reservoirs to address critical issues in integrated reserve enhancement. This paper proposes an improved consolidation index model. This method not only takes into account the consolidation degree in sandstone but also incorporates the influence of porosity on the consolidation index. It exhibits higher parameter stability and stronger calculation accuracy. Through rock physics analysis, a rock physics template suitable for the quantitative characterization of such reservoirs is constructed, with anisotropic parameters integrated into it, laying a foundation for prestack inversion. Using wide-azimuth offset vector tile (OVT) data, elastic parameter volumes across different azimuths are inverted. Through elliptical fitting, anisotropic parameters for compressional and shear waves are obtained. This approach quantitatively describes porosity distribution and fracture networks within the study area, offering guidance for the comprehensive evaluation of high-quality tight sand-gravel reservoirs.